CAPITAL STRUCTURE, LIQUIDITY, AND FIRM SIZE AS DETERMINANTS OF PROFITABILITY: EVIDENCE FROM PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIA STOCK EXCHANGE, 2020–2023 - Krisnayanthi, Ni Made Dian; Gunadi, I Gusti Ngurah Bagus; Astiti, Ni Putu Yeni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
The property and real estate sector in Indonesia has great growth potential and is a prime choice for investors. However, this sector faces economic challenges and intense competition, making profitability an important indicator for attracting investment. This study aims to determine the effect of capital structure, liquidity, and company size on profitability in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The research population includes all property and real estate companies listed on the IDX during that period, with purposive sampling techniques resulting in 20 companies meeting the criteria. The data analysis technique used is multiple linear regression. The results of the study indicate that capital structure has a negative and significant effect on profitability, liquidity has a positive and significant effect, while company size does not have a significant effect on Profitability.